Effects of lipid extraction on the isotopic values of sea turtle bone collagen - L Medeiros (Inter-Research, 2015)
Many stable isotope analysis (SIA) studies aim to track protein, which is assimilated in animal tissues from their food sources, to assess feeding ecology, movements, and ontogenetic shifts of marine animals. Lipids are known to be a potential source of bias because they are depleted in 13C compared to 12C. Although lipids are usually removed before SIA, there is a lack of standardized analytical protocols for this procedure. We tested the effects of lipid extraction with 2 chemical solvents (chloroform-methanol and petroleum ether) in the humeri of the loggerhead sea turtle Caretta caretta to establish a standard protocol for processing the bone collagen of marine animals and to develop a mathematical correction. In both lipid extraction treatments, δ13C values were higher than the control, but only lipid extraction with chloroform-methanol showed significant differences. By contrast, the δ15N values were not affected by lipid extraction treatments with either solvent. The linear regression between the C:Nbulk ratio and Δ13C was not significant, which does not support the assumption that there is a predictable relationship between the C:N ratio and lipid content. Nevertheless, a significant positive relationship between Δ13C and δ13Cbulk was observed, but such a model is not recommended as a mathematical lipid correction method because the model efficiency had a negative value, which indicates that the mean value of δ13Cle is a better predictor than the model itself. These results suggest that lipid extraction should be taken into account in SIA of bone collagen tissues for accurate δ13C determination.